Risk Factors for Primary Postpartum Hemorrhage in Vaginal Delivery - Rai, Subash; Dangal, Ganesh; Jaiswal, Ekta (Journal of Nepal Health Research Council, 2024)
Background: Postpartum hemorrhage is an emergency, condition encountered in obstetric cases. It is an acute life-threatening situation and needs an immediate and rapid management. Postpartum hemorrhage is leading cause of maternal mortality and morbidity worldwide, with more commonly affecting women of developing countries. Accurate assessment of blood loss, identification of risk factors and timely recognition of postpartum hemorrhage remain major challenge in obstetrics. Different risk factors like hypertensive disorder in pregnancy, antepartum hemorrhage, anemia, big baby, polyhydramnios, multiple pregnancy, obesity, augmented/prolonged labor are risk factors for primary postpartum hemorrhage. The objective of this study was to identify the various risk factors associated with primary postpartum hemorrhage, in Paropakar Maternity and Women’s Hospital (PMWH), which is biggest institute in country for holding records of maximum number of deliveries. Methods: A cross sectional study was conducted over a period of 3 months between March 2023 to May 2023 on 72 patients. Women with term pregnancy who experienced primary PPH were analyzed for different risk factors. Similarly, incidence of postpartum hemorrhage according to age, parity, gestational age, types of labor, types of vaginal delivery and causes of postpartum hemorrhage were studied. The results were then analyzed. Results: The incidence of primary PPH during the study was 3%. Majority of cases of PPH were in age group of 20-24 (44.4%), followed by age group (25-29). Most of cases (50%) were of gravidity 2 to 3, followed by primigravida (45.8%). There was equal distribution of PPH in gestation age (37-39+6) WOG to (40-41+6) WOG. There were no risk factors associated with occurrence of PPH in 56%. Hypertensive disorder of pregnancy, anemia, APH, multiple pregnancy, fetal macrosomia, polyhydramnios and obesity are associated risk factors for PPH. Among risk factors associated with PPH, hypertensive disorder of pregnancy was most common risk factors (40.6%), followed by maternal anemia (25%), multiple pregnancy (12.5%), APH (6.3%) fetal macrosomia (6.3%), maternal obesity (6.3%), polyhydramnios (3.1%). PPH was more common in augmented labor (43%), followed by induced labor (29.2%) and spontaneous labor (27.8%). In this study most women ( 72.2%) experienced blood loss of 500-1000 ml. And most common cause of PPH was atony (83.3%) followed by genital tract injury (14%) and retained tissues (2.7%). Conclusions: In many cases, PPH can’t be predicted fully as many cases of PPH occur without vivid risk factors, as in this study 56% women experiencing PPH had no associated antenatal risk factors. Antenatal risk factors like hypertensive disorder of pregnancy, maternal anemia, twin pregnancy, APH, macrosomia, obesity are common risk factors for PPH. Similarly induced and augmented labor and instrumental delivery can lead to PPH. Keywords: Postpartum haemorrhage, risk factors, vaginal delivery